Role of teacher humor in teaching research methodology within the Vietnamese context - Thanh Thao Le; Trut Thuy Pham (Cogent Arts & Humanities)
This qualitative study delves into the role of humor as employed by teachers in the teaching of research methodology, set within the Vietnamese context. Through semi-structured interviews with 24 Vietnamese English-major students across two institutions, the research sought to understand humor’s multifaceted impacts on learning outcomes and classroom dynamics. Findings revealed that humor promisingly enhances engagement and aids memory retention of complex concepts. However, cultural nuances play a pivotal role in how humor is received, with the potential for misinterpretation when not resonating with students’ cultural backgrounds. The study also highlighted humor’s capacity to bridge the teacher-student hierarchical gap, foster peer interactions, and alleviate anxiety, thereby boosting confidence. Conversely, potential pitfalls emerged, pointing to humor’s capacity to distract or inadvertently exclude when not judiciously applied. These findings have some implications for pedagogical practices, emphasizing the need for cultural sensitivity, and offer a foundation for future research in diverse educational settings.